Non-degradable anti-protein adsorption material as well as preparation method and application thereof
By using block polymers with silane coupling agents as crosslinking sites in anti-protein adsorption materials, combined with controllable/active radical polymerization reaction, the problem of difficult to take into account both the anti-protein adsorption properties and the mechanical properties in traditional technology is solved. , achieving efficient and stable anti-protein adsorption effect and good mechanical properties.
Patent Information
- Application Number
- CN202411607299.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-11-12
AI Technical Summary
The prior art lacks simple and easy-to-use surface coating modification methods in terms of protein adsorption, and it is difficult to take into account the mechanical properties and anti-fouling characteristics of the bulk materials prepared by traditional anti-fouling hydrophilic polymers.
Using block polymers with silane coupling agent as the crosslinking site, non-degradable anti-protein adsorption materials are synthesized through a controlled/active radical polymerization reaction. The molecular chain composition of the material includes polyethylene glycol hydrophilic chain segments, The hydrophobic chain segments and crosslinked chain segments can adjust the proportion of molecular structure and the ratio of crosslinked monomers to achieve the mechanical strength control of the material and the improvement of the anti-fouling performance.
It realizes materials with excellent anti-protein adsorption properties at a lower PEG content, while ensuring excellent processability and mechanical properties of the bulk materials, and is suitable for long-term implantation medical devices.
Smart Images

Figure CN119463074A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of biomedical materials, and in particular to a non-degradable protein-resistant adsorption material and a preparation method and application thereof. Background Art
[0002] In recent years, people's demand for implantable medical devices has continued to grow. Cardiovascular stents, orthopedic prostheses, etc. have been widely used in clinical practice; cutting-edge products such as biochemical signal sensors and brain-computer interfaces have also been continuously developed and improved. However, when foreign implants enter the human body and come into contact with blood or body fluids, they will trigger a foreign body reaction in a very short time. The adsorption of plasma proteins will induce the formation of thrombi, resulting in reduced efficacy and safety of the device; the collagen fiber capsule formed by the foreign body reaction will not only cause tissue deformation and patient pain, but also affect the sensitivity and service life of the sensor. In addition, protein adsorption can also cause bacteria to colonize on the surface of implants in the body. Current anti-inflammatory and anticoagulant drugs and antibiotic-assisted treatments will produce many side effects and bring other health risks.
[0003] Going back to the source, the nonspecific adhesion of proteins to the surface of materials is a prerequisite for foreign body reaction. Compared with hydrophilic interfaces, proteins are more easily adsorbed on hydrophobic substrates. Therefore, hydrophilic chemical modifiers can be modified on hydrophobic interfaces by means of physical adsorption, interfacial gel network construction, layer-by-layer self-assembly (LBL), surface grafting and other technologies, and the anti-fouling performance of materials can be improved by relying on hydrophilic molecules to form a hydration layer. Among them, the physical adsorption strategy has poor long-term stability; the application of high-water-content interfacial gel layers in blood contact devices poses a risk of platelet damage; LBL is generally not suitable for substrates with small volumes or that are not tolerant to water environments, and the immersion assembly process is time-consuming and labor-intensive, so its application is limited. In comparison, the surface grafting technology of strong hydration functional molecules such as polyethylene glycol (PEG) and zwitterionic compounds (such as phosphorylcholine) is relatively mature, and the grafting of PEG or polyethylene oxide (PEO) molecular brushes on the surface of materials to achieve hydrophilic modification is considered to be the gold standard for anti-fouling applications. However, the anti-fouling performance of this anti-protein adhesion surface based on PEG molecular brushes is strongly dependent on the grafting density and uniformity of PEG. Any tiny defect on the surface of the material may make the design of the anti-fouling coating invalid. In order to achieve high-density preparation of PEG molecular brush coatings on the surface of materials, the preparation methods of "grafting to" and "grafting from" are currently used. Before preparation, the base material needs to be physically and chemically modified, and the implementation process is relatively cumbersome. Compared with the characteristics of difficult preparation and easy failure of anti-fouling coatings, the exposure of the internal anti-fouling structure of the bulk material during service can effectively compensate for the damaged anti-fouling performance at the surface interface. However, gel materials prepared from polymers with strong hydration ability usually have poor mechanical properties due to their high water content, which seriously limits their use as functional implants in the body. In particular, for medical devices with long-term implantation requirements, the long-term stability of the anti-fouling performance of the coating and the bulk material in the in vivo environment is crucial. Extending the service life of the device and reducing the frequency of replacement can effectively reduce the treatment pain of patients and improve patient compliance.
[0004] From this point of view, the important technical bottlenecks of anti-protein adhesion of implantable medical devices are: 1. Due to the limitations of traditional anti-protein adhesion molecules, there is currently a lack of simple and stable surface coating modification methods; 2. Traditional anti-fouling hydrophilic polymers have a large swelling rate when preparing bulk materials, and the initial shape is difficult to maintain, and it is difficult to take into account both mechanical properties and anti-fouling properties. In summary, for materials and devices with long-term implantation needs, there is an urgent need to develop a new type of non-degradable anti-fouling molecule and related implementation technologies. When this molecule is used in anti-fouling coatings, surface modification can be completed easily and quickly. When used as a bulk material, the mechanical strength is adjustable, the application range is wide, and it has the ability to continuously resist protein adsorption in subsequent application scenarios. Summary of the invention
[0005] In view of the above technical problems and the deficiencies in the art, the present invention provides a non-degradable anti-protein adsorption material and a preparation method and application thereof.
[0006] The specific technical solutions are as follows:
[0007] [1] A non-degradable anti-protein adsorption material, which is a block polymer with a silane coupling agent as a cross-linking site or a material formed by cross-linking a material including the block polymer.
[0008] The block polymer is non-degradable, and the molecular chain composition includes a polyethylene glycol hydrophilic segment, a hydrophobic segment introduced by a hydrophobic monomer, and a cross-linked segment introduced by a cross-linked monomer, wherein the polyethylene glycol hydrophilic segment is located between the hydrophobic segments, and the hydrophobic segments include one or more combinations of methacrylate segments and aromatic substituted polyolefin segments. The cross-linked monomer is a silane coupling agent with a carbon-carbon double bond. The cross-linked monomer can be embedded in the hydrophobic segment and / or form a cross-linked segment at the end of the molecular chain during the polymerization process to form the block polymer to provide the cross-linking site required for the subsequent reaction, that is, the hydrophobic segment may contain and / or not contain a cross-linked monomer. Further, the aromatic substituted polyolefin segment can be introduced by an aromatic substituted olefin, wherein the olefin can be a C1-C4 olefin, such as ethylene, butene, etc. The aromatic group can be a phenyl group, etc. Optionally, the molar ratio of the hydrophobic monomer to the cross-linked monomer is 100:(5-20).
[0009] The number average molecular weight of the polyethylene glycol hydrophilic segment may be 100 to 10,000 g / mol, and is preferably 800 to 4,000 g / mol in consideration of the material properties and antifouling performance after synthesis and processing.
[0010] The mass proportion of the hydrophilic segment of polyethylene glycol in the block polymer can be 5% to 50%, preferably 10% to 40%, such as 20%, 30%, etc. Such a strict molecular structure proportion mainly considers two factors: 1. The coverage of the hydrated PEG chain has a great influence on the anti-fouling performance of the coating. If the PEG content is too low, the hydration layer cannot completely cover the coating surface, and the protein will adhere to the non-hydrated area, resulting in coating failure; 2. When the PEG content is too high, due to its strong hydrophilicity, the material absorbs water and swells in the aqueous environment to form a hydrated coating containing a hydrogel or a gel-like hydrate. During the swelling process, the PEG chain loses its specific anti-fouling molecular structure due to excessive stretching, and its mechanical properties are poor when used as a bulk material.
[0011] The sum of the mass proportions of the hydrophobic segments and the cross-linked segments in the block polymer may be 50% to 95%, preferably 60% to 90%, such as 70%, 80%, etc.
[0012] In some embodiments, in the block polymer, the sum of the mass proportions of the polyethylene glycol hydrophilic segment, the hydrophobic segment, and the cross-linked segment may be 100%.
[0013] The present invention can adopt controlled / active free radical polymerization, and under the action of terminal functionalized polyethylene glycol, initiator, catalyst, ligand and other reagents, the monomer can undergo polymerization reaction to obtain block polymer. Considering the difference in reactivity between the crosslinking monomer and the olefin monomer used, if the two undergo random copolymerization under the reaction conditions, one-step feeding can be adopted; if the olefin monomer tends to self-polymerize, a segmented reaction can be carried out, and after the crosslinking monomer is fully reacted, the crosslinking monomer is added to the two ends of the existing polymer chain for further polymerization, and finally a block polymer with a silane coupling agent as a crosslinking site is obtained.
[0014] The hydrophobic monomer may include an olefinic monomer. In some embodiments, the olefinic monomer may include at least one of methyl methacrylate, ethyl methacrylate, propyl methacrylate, butyl methacrylate, hexyl methacrylate, octyl methacrylate, lauryl methacrylate, styrene, phenyl butene, and the like.
[0015] The crosslinking monomer may include at least one of 3-(methacryloyloxy)propyltrimethoxysilane, methacryloxypropyltriethoxysilane, 3-trimethoxysilane propyl acrylate, allyltrimethylsilane, vinyltri(β-methoxyethoxy)silane, vinyltrimethoxysilane, and A-151 silane coupling agent.
[0016] The precursor of the terminal functionalized polyethylene glycol may include at least one of dihydroxyl-terminated polyethylene glycol, monomethyl ether polyethylene glycol, and n-arm polyethylene glycol, wherein n≥3, and may be processed into a macromolecular initiator or a RAFT agent according to different synthesis methods.
[0017] The synthesis method of the non-degradable block polymer material of the present invention includes controlled radical polymerization pathways such as atom transfer radical polymerization (ATRP), reversible addition-fragmentation transfer (RAFT) method and other effective methods for preparing block polymers. Compared with traditional free radical polymerization, the key to controlled radical polymerization lies in the dynamic balance between growing chain radicals and dormant species. The rapid exchange between active species and dormant species enables the molecular weight, molecular weight distribution and polymer structure of the polymer to be well controlled in controlled radical polymerization, which is crucial for the precise preparation and performance of the above-mentioned anti-fouling block polymers. When ATRP is used, the dormant species / initiator mainly exists in the form of organic halide RX (X is a halogen atom), and the polymer can participate in the reaction as a macromolecular initiator after halogenation. During the reaction, the dormant species are intermittently activated by the activator Mt m / L(Mt m represents a transition metal compound in a low reduction valence state m, which is a catalyst; L is a ligand) activated to form a propagating free radical R· and a passivating agent X-Mt m+1 / L(Mt m+1Represents a transition metal compound in a high oxidation state m+1). R· acts as an active species to initiate polymerization, and the passivator reacts with R· in reverse to re-form dormant species and activators. This process reduces the concentration of free radicals and inhibits chain termination reactions, showing controlled polymerization. RAFT polymerization is initiated by conventional free radical initiators such as azobisisobutyronitrile in the presence of a chain transfer agent (RAFT agent). Its core is regeneration transfer, and it also has strong molecular design capabilities.
[0018] The block polymer can be obtained by controlled / active radical polymerization. The raw material composition of the controlled / active radical polymerization may include olefin monomers, crosslinking monomers and end-functionalized polyethylene glycol. The olefin monomers can be used for polymerization to form hydrophobic segments. The end-functionalized polyethylene glycol (which can be used as an initiator in some embodiments) can be used for reaction to form polyethylene glycol hydrophilic segments. The end groups in the end-functionalized polyethylene glycol can be functionalized into one or more combinations of halogen-containing end groups (such as halogens, etc.), dithioester end groups, double bond-containing end groups, etc. Among them, the halogen-containing end groups can be used for ATRP polymerization, and the dithioester end groups can be used for RAFT polymerization.
[0019] In some embodiments, the controlled / active radical polymerization reaction may be an atom transfer radical polymerization (ATRP) reaction. Accordingly, the raw material may also include a catalyst and a ligand. The catalyst may include cuprous halides, such as cuprous chloride, cuprous bromide, etc. The amount of the catalyst added may be 1.1 to 3 times the molar amount of the functionalized end group (e.g., halogen-containing end group) in the end-functionalized polyethylene glycol. The ligand is mainly used for solubilizing the transition metal salt in an organic solvent and adjusting the oxidation-reduction potential of the metal center. The ligand may include at least one of 2,2'-bipyridine, pentamethyldiethylenetriamine, etc. The amount of the ligand added may be 2.5 to 7.5 times the molar amount of the functionalized end group (e.g., halogen-containing end group) in the end-functionalized polyethylene glycol. Other synthesis methods may select corresponding initiators and related reagents according to specific circumstances.
[0020] To ensure the successful introduction of the silane coupling agent on the polymer chain, taking into account the influence of the monomer reactivity ratio, when preparing the block polymer by controlled / active free radical polymerization, the amount of the cross-linking monomer added in the one-step feeding can be 5% to 20% of the molar amount of the olefin monomer in the same batch.
[0021] In the present invention, the temperature of the controlled / living radical polymerization reaction can be 50-75° C., such as 70° C., 100° C., etc., and the time can be 5-20 hours, such as 6 hours, 12 hours, etc.
[0022] In the present invention, the controlled / living free radical polymerization reaction can be bulk polymerization, solution polymerization, etc. The selected solvent can be tetrahydrofuran, N,N-dimethylformamide, ethanol, toluene, etc., and it is preferred to use ultra-dry reagents.
[0023] In the present invention, the temperature for cross-linking the material may be 45-55°C, such as 50°C.
[0024] [2] The method for preparing the non-degradable protein-resistant adsorption material according to [1] comprises:
[0025] preparing olefin monomers, cross-linking monomers and terminal functionalized polyethylene glycol, wherein the olefin monomers are used for polymerization to form hydrophobic segments, and the terminal functionalized polyethylene glycol is used for reaction to form polyethylene glycol hydrophilic segments;
[0026] The block polymer is obtained by subjecting raw materials including olefin monomers, crosslinking monomers and terminal functionalized polyethylene glycol to controlled / living free radical polymerization; or,
[0027] After the block polymer is obtained according to the above process, the non-degradable protein-resistant adsorption material is further obtained by thermal cross-linking.
[0028] [3] Application of the non-degradable anti-protein adsorption material according to [1] in the field of anti-protein adsorption. The non-degradable anti-protein adsorption material can be used as a bulk material and / or a coating material for anti-protein adsorption. When used as a bulk material, a product of a specific shape can be obtained by conventional polymer processing methods such as molding, extrusion, injection molding, casting and 3D printing. Compared with the gel material prepared by hydrophilic polymer, the introduction of hydrophobic segments can reduce its swelling rate in an aqueous environment, the entanglement between hydrophobic chains can enhance the cohesive energy of the polymer material, and the silane coupling molecules at both ends of the polymer can be internally cross-linked by heating to ensure the chemical and mechanical stability of the product. By adjusting the degree of polymerization and mass proportion of the hydrophilic and hydrophobic segments, as well as the ratio of the cross-linking monomer to the olefin monomer, the mechanical strength of the bulk material can be regulated. When used as an anti-protein adsorption coating material, the thickness of the coating can be 0.01 to 50 microns, and an exemplary preparation method may include: introducing (hydroxyl, etc.) active groups into the surface to be modified (for example, by pretreatment methods such as plasma), dissolving the non-degradable anti-protein adsorption material in a solvent (which may include at least one of dichloromethane, anhydrous ethanol, tetrahydrofuran, ethyl acetate, etc.); in some cases, the mass fraction of the non-degradable anti-protein adsorption material in the resulting solution may be 0.1% to 50%; then, the resulting solution (which may be applied by spin coating, spray coating, dip coating, etc.) is uniformly coated on the surface to be modified, cross-linked and cured under heat treatment conditions, thereby enhancing the stability of the coating and achieving close bonding with the substrate material, thereby constructing a non-degradable block polymer anti-fouling coating on the surface to be modified.
[0029] The coating has excellent anti-protein adsorption ability, and its internal mechanism is: the block polymer is composed of hydrophilic PEG segments, hydrophobic segments such as methacrylate, and olefin cross-linking monomers. After forming the coating and thermal cross-linking, the polymer will form a specific micro-nano structure on the surface of the coating, and the hydrophilic and hydrophobic water areas will remain intertwined at the molecular level. In the aqueous environment, the hydrophobic segments are closely attached to the material base inward, and the hydrophilic PEG segments are extended outward, stably exposed to the surface, and form a strong bond with water molecules through hydrogen bond interactions, constructing a strong surface hydration layer, thereby hindering the adhesion of proteins, platelets and bacteria on the coating surface.
[0030] Compared with the prior art, the present invention has the following beneficial effects:
[0031] 1. After optimization, the molecular weight of PEG and its proportion in the above-mentioned polymer as a whole are strictly limited: the number average molecular weight of PEG is 800-4000g / mol, and the mass of PEG is 10%-40% of the total mass of the overall polymer; the present invention utilizes the unique molecular structure of the amphiphilic block polymer and its intrinsic self-assembly behavior, so that the hydrophilic domain and the hydrophobic domain spontaneously form a staggered and closely packed state at the molecular level and a uniformly mixed state during the construction of the bulk material or the preparation of the polymer coating, and the PEG chain segment in the aqueous environment expands outward and is in a strongly hydrated state; in addition, the silane coupling agent on the hydrophobic chain segment of the polymer cross-links and solidifies under thermal initiation conditions to stabilize the mechanical properties of the material and strengthen the interface bonding. As a result, the anti-fouling material can have both the mechanical properties of the bulk material and excellent anti-fouling properties under simple and easy implementation conditions. Based on the above design, the anti-protein adsorption material prepared by the present invention can achieve a protein adsorption amount less than or equal to the adsorption amount of the pure hydrophilic molecules closely arranged material at a lower PEG content, and ensure the excellent processability and mechanical properties of the bulk material. It should be noted that the present invention focuses on limiting this type of unique molecular structure, specific PEG molecular weight, and the proportion of PEG blocks in the overall polymer, rather than the material synthesis method. Any synthesis method that can obtain such a molecule, and the final product is similar to the molecular structure we protect, is within the scope of protection of the present invention.
[0032] 2. Compared with the diblock copolymer based on polyethylene glycol monomethyl ether, the unique triblock amphiphilic molecular structure of the present invention strictly limits the polyethylene glycol block in the polymer between the hydrophobic segments such as methacrylate, showing double-end fixation. The outward expansion of the PEG molecular chain in the aqueous environment can better adapt to external compression and reduce the permeability of proteins, so it has better anti-protein adsorption performance than the diblock polymer of the same mass ratio.
[0033] 3. The anti-protein adsorption polymer material obtained by the present invention has good processability, and the main material can be obtained by molding, extrusion, injection molding, casting and 3D printing; the anti-adsorption coating can also be prepared by spin coating, dip coating, spraying and other processing methods, so its applicability is far greater than most anti-protein adsorption materials on the market. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 This is a graph showing the effect of the mass ratio of polyethylene glycol blocks in block polymers on the material's anti-protein adsorption performance;
[0035] Figure 2 This is a comparison chart of the anti-protein adsorption performance of the diblock polymer material of Comparative Example 1 and the triblock polymer material of Example 2 in the form of coating;
[0036] Figure 3 This is a comparison chart of the anti-platelet adhesion performance of the base material TPU, the coating of comparative example 1 and the coating of example 2;
[0037] Figure 4 This is a comparison chart of the tensile strength between PEGDA and the triblock polymer material of Example 2. DETAILED DESCRIPTION
[0038] The present invention will be further described below in conjunction with the accompanying drawings and specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention.
[0039] Unless otherwise specified, the unit of number average molecular weight is g / mol.
[0040] Example 1
[0041] Preparation of PBMA / SCA-PEG-PBMA / SCA-105 (PBEB105-Si) non-degradable antifouling materials and coatings
[0042] 1. Preparation of macromolecular initiator (double-terminal brominated PEG, Br-PEG-Br):
[0043] Take 3.63g of double-terminated hydroxyl polyethylene glycol with a number average molecular weight of 1000 and dissolve it in 30mL of dichloromethane (DCM) in a 100mL round-bottom flask, and add a certain amount of anhydrous sodium sulfate to bind the water in the system. Add 3.6mL of triethylamine TEA, an acid binding agent, to the flask, add 2.7mL of bromoisobutyryl bromide dropwise to the flask under ice-water bath conditions, and then react at room temperature for 12h. After terminating the reaction, use extraction to remove impurities, and precipitate with ice ether to obtain the product Br-PEG-Br.
[0044] 2. Synthesis of triblock polymers with silane coupling agents as crosslinking sites:
[0045] The reaction needs to be carried out under anhydrous and oxygen-free conditions. The 100mL reaction tube is connected to a double-row tube, and the bottle is baked with a hot spray gun under vacuum conditions to remove water. After three gas exchanges, argon protection is maintained. The mass proportion of the polyethylene glycol block in PBEB105-Si is 20%. According to calculations, 140mg of the catalyst cuprous bromide (CuBr), 650mg of Br-PEG-Br, 1.95mL of butyl methacrylate monomer (BMA), and 285μL of anhydrous ethanol solution of 3-(isobutylene acyloxy)propyltrimethoxysilane (TMSPMA) monomer are added to the reaction tube in sequence. After a freeze-thaw operation, 400mg of 2,2'-bipyridine (Bpy) ligand is added, and freeze-thaw is continued for three times to fully remove oxygen. The reaction system is then placed in a 70℃ oil bath for continuous reaction for about 12h, the reaction is terminated and post-processed to obtain a triblock polymer (PBEB105-Si) with a number average molecular weight of about 5000.
[0046] 3. Preparation of biological antifouling coating and bulk materials:
[0047] Take the substrate to be modified (silicon wafer, glass sheet, etc.) and perform plasma cleaning; dissolve the polymer PBEB105-Si in tetrahydrofuran (THF) to prepare a polymer solution concentration of 10 mg / mL, and use spin coating technology to obtain a uniform coating with nanometer thickness on the substrate, and then place it in a hot oven at 50°C for 1 hour for cross-linking and curing.
[0048] For the preparation of anti-fouling bulk materials, the casting method is taken as an example: take a mold of appropriate size (such as a tetrafluoroethylene mold, etc.), dissolve the polymer PBEB105-Si in THF, prepare a 400 mg / mL polymer concentrated solution, take an appropriate amount of polymer solution to fill the mold, evaporate the solvent under natural conditions, and then place it in a hot oven at 50°C for 1 hour for cross-linking and curing.
[0049] Example 2
[0050] Preparation of PBMA / SCA-PEG-PBMA / SCA-110 (PBEB110-Si) non-degradable antifouling materials and coatings
[0051] 1. The preparation process of the macromolecular initiator (Br-PEG-Br) is the same as that in Example 1.
[0052] 2. Synthesis of triblock polymers with silane coupling agents as crosslinking sites:
[0053] The reaction needs to be carried out under anhydrous and oxygen-free conditions. The 100mL reaction tube is connected to a double-row tube, and the bottle is baked with a hot spray gun under vacuum conditions to remove water. After three gas exchanges, argon protection is maintained. The mass proportion of the polyethylene glycol block in PBEB110-Si is 10%. According to calculations, 136mg of the catalyst CuBr, 612mg of Br-PEG-Br, 4.05mL of BMA monomer, and 605μL of TMSPMA monomer in anhydrous ethanol solution are added to the reaction tube in sequence. After one freeze-thaw, 368mg of the ligand Bpy is added, and three freeze-thaw cycles are continued to fully remove oxygen. The reaction system is then placed in a 70°C oil bath for continuous reaction for about 12 hours, the reaction is terminated and post-processed, and a triblock polymer (PBEB110-Si) with a number average molecular weight of about 10,000 can be obtained.
[0054] 3. Preparation of biological antifouling coating and bulk materials:
[0055] Take the substrate to be modified (silicon wafer, glass wafer, etc.) and perform plasma cleaning; dissolve the polymer PBEB110-Si in THF to prepare a polymer solution concentration of 10 mg / mL, and use spin coating technology to obtain a uniform coating with nanometer thickness on the substrate, and then place it in a hot oven at 50°C for 1 hour for cross-linking and curing.
[0056] For the preparation of anti-fouling bulk materials, the casting method is taken as an example: take a mold of appropriate size (such as a tetrafluoroethylene mold, etc.), dissolve the polymer PBEB110-Si in THF, prepare a 400 mg / mL polymer concentrated solution, take an appropriate amount of polymer solution to fill the mold, evaporate the solvent under natural conditions, and then place it in a hot oven at 50°C for 1 hour for cross-linking and curing.
[0057] Example 3
[0058] Preparation of PBMA / SCA-PEG-PBMA / SCA-120 (PBEB120-Si) non-degradable antifouling materials and coatings
[0059] 1. The preparation process of the macromolecular initiator (Br-PEG-Br) is the same as that in Example 1.
[0060] 2. Synthesis of triblock polymers with silane coupling agents as crosslinking sites:
[0061] The reaction needs to be carried out under anhydrous and oxygen-free conditions. The 100mL reaction tube is connected to a double-row tube, and the bottle is baked with a hot spray gun under vacuum conditions to remove water. After three gas exchanges, argon protection is maintained. The mass proportion of the polyethylene glycol block in PBEB120-Si is 5%. According to calculations, 70mg of the catalyst CuBr, 307mg of Br-PEG-Br, 4.3mL of BMA monomer, and 640μL of TMSPMA monomer in anhydrous ethanol solution are added to the reaction tube in sequence. After one freeze-thaw, 190mg of the ligand Bpy is added, and three freeze-thaw cycles are continued to fully remove oxygen. The reaction system is then placed in a 70°C oil bath for continuous reaction for about 12 hours, the reaction is terminated and post-processed to obtain a triblock polymer (PBEB120-Si) with a number average molecular weight of about 20,000.
[0062] 3. Preparation of biological antifouling coating and bulk materials:
[0063] Take the substrate to be modified (silicon wafer, glass wafer, etc.) and perform plasma cleaning; dissolve the polymer PBEB120-Si in THF to prepare a polymer solution concentration of 10 mg / mL, and use spin coating technology to obtain a uniform coating with nanometer thickness on the substrate, and then place it in a hot oven at 50°C for 1 hour for cross-linking and curing.
[0064] For the preparation of anti-fouling bulk materials, the casting method is taken as an example: take a mold of appropriate size (such as a tetrafluoroethylene mold, etc.), dissolve the polymer PBEB120-Si in THF, prepare a 400 mg / mL polymer concentrated solution, take an appropriate amount of polymer solution to fill the mold, evaporate the solvent under natural conditions, and then place it in a hot oven at 50°C for 1 hour for cross-linking and curing.
[0065] Example 4
[0066] Preparation of PBMA / SCA-PEG-PBMA / SCA-103 (PBEB103-Si) non-degradable antifouling materials and coatings
[0067] 1. The preparation process of the macromolecular initiator (Br-PEG-Br) is the same as that in Example 1.
[0068] 2. Synthesis of triblock polymers with silane coupling agents as crosslinking sites:
[0069] The reaction needs to be carried out under anhydrous and oxygen-free conditions. The 100mL reaction tube is connected to a double-row tube, and the bottle is baked with a hot spray gun under vacuum conditions to remove water. After three gas exchanges, argon protection is maintained. The mass proportion of the polyethylene glycol block in PBEB103-Si is about 30%. According to calculations, 95mg of the catalyst CuBr, 417mg of Br-PEG-Br, 980μL of BMA monomer, and 100μL of TMSPMA monomer in anhydrous ethanol solution are added to the reaction tube in sequence. After one freeze-thaw, 200mg of the ligand Bpy is added, and three freeze-thaw cycles are continued to fully deoxygenate. The reaction system is then placed in a 70°C oil bath for continuous reaction for about 12 hours, the reaction is terminated and post-processed to obtain a triblock polymer (PBEB103-Si) with a number average molecular weight of about 3000.
[0070] 3. Preparation of biological antifouling coating and bulk materials:
[0071] Take the substrate to be modified (silicon wafer, glass wafer, etc.) and perform plasma cleaning; dissolve the polymer PBEB103-Si in THF to prepare a polymer solution concentration of 10 mg / mL, and use spin coating technology to obtain a uniform coating with nanometer thickness on the substrate, and then place it in a hot oven at 50°C for 1 hour for cross-linking and curing.
[0072] For the preparation of anti-fouling bulk materials, the casting method is taken as an example: take a mold of appropriate size (such as a tetrafluoroethylene mold, etc.), dissolve the polymer PBEB103-Si in THF, prepare a 400 mg / mL polymer concentrated solution, take an appropriate amount of polymer solution to fill the mold, evaporate the solvent under natural conditions, and then place it in a hot oven at 50°C for 1 hour for cross-linking and curing.
[0073] Example 5
[0074] Preparation of PBMA / SCA-PEG-PBMA / SCA-1024 (PBEB1024-Si) non-degradable antifouling materials and coatings
[0075] 1. The preparation process of the macromolecular initiator (Br-PEG-Br) is the same as that in Example 1.
[0076] 2. Synthesis of triblock polymers with silane coupling agents as crosslinking sites:
[0077] The reaction needs to be carried out under anhydrous and oxygen-free conditions. The 100mL reaction tube is connected to a double-row tube, and the bottle is baked with a hot spray gun under vacuum conditions to remove water. After three gas exchanges, argon protection is maintained. The mass proportion of the polyethylene glycol block in PBEB1024-Si is about 40%. According to calculations, 135mg of the catalyst CuBr, 575mg of Br-PEG-Br, 785μL of BMA monomer, and 156μL of TMSPMA monomer in anhydrous ethanol solution are added to the reaction tube in sequence. After one freeze-thaw, 280mg of the ligand Bpy is added, and three freeze-thaw cycles are continued to fully remove oxygen. The reaction system is then placed in a 70°C oil bath for continuous reaction for about 12 hours, the reaction is terminated and post-processed, and a triblock polymer (PBEB1024-Si) with a number average molecular weight of about 2400 can be obtained.
[0078] 3. Preparation of biological antifouling coating and bulk materials:
[0079] Take the substrate to be modified (silicon wafer, glass wafer, etc.) and perform plasma cleaning; dissolve the polymer PBEB1024-Si in THF to prepare a polymer solution concentration of 10 mg / mL, and use spin coating technology to obtain a uniform coating with nanometer thickness on the substrate, and then place it in a hot oven at 50°C for 1 hour for cross-linking and curing.
[0080] For the preparation of anti-fouling bulk materials, the casting method is taken as an example: take a mold of appropriate size (such as a tetrafluoroethylene mold, etc.), dissolve the polymer PBEB1024-Si in THF, prepare a 400 mg / mL polymer concentrated solution, take an appropriate amount of polymer solution to fill the mold, evaporate the solvent under natural conditions, and then place it in a hot oven at 50°C for 1 hour for cross-linking and curing.
[0081] Example 6
[0082] Preparation of PBMA / SCA-PEG-PBMA / SCA-102 (PBEB102-Si) non-degradable antifouling materials and coatings
[0083] 1. The preparation process of the macromolecular initiator (Br-PEG-Br) is the same as that in Example 1.
[0084] 2. Synthesis of triblock polymers with silane coupling agents as crosslinking sites:
[0085] The reaction needs to be carried out under anhydrous and oxygen-free conditions. The 100mL reaction tube is connected to a double-row tube, and the bottle is baked with a hot spray gun under vacuum conditions to remove water. After three gas exchanges, argon protection is maintained. The mass proportion of the polyethylene glycol block in PBEB102-Si is about 50%. According to calculations, 60mg of the catalyst CuBr, 255mg of Br-PEG-Br, 165μL of BMA monomer, and 105μL of TMSPMA monomer in anhydrous ethanol solution are added to the reaction tube in sequence. After one freeze-thaw, 130mg of the ligand Bpy is added, and three freeze-thaw cycles are continued to fully remove oxygen. The reaction system is then placed in a 70°C oil bath for continuous reaction for about 12 hours, the reaction is terminated and post-processed, and a triblock polymer (PBEB102-Si) with a number average molecular weight of about 2000 can be obtained.
[0086] 3. Preparation of biological antifouling coating and bulk materials:
[0087] Take the substrate to be modified (silicon wafer, glass sheet, etc.) and perform plasma cleaning; dissolve the polymer PBEB102-Si in THF to prepare a polymer solution concentration of 10 mg / mL, use spin coating technology to obtain a uniform coating with nanometer thickness on the substrate, and then place it in a hot oven at 50°C for 1 hour for cross-linking and curing.
[0088] For the preparation of anti-fouling bulk materials, the casting method is taken as an example: take a mold of appropriate size (such as a tetrafluoroethylene mold, etc.), dissolve the polymer PBEB102-Si in THF, prepare a 400 mg / mL polymer concentrated solution, take an appropriate amount of polymer solution to fill the mold, evaporate the solvent under natural conditions, and then place it in a hot oven at 50°C for 1 hour for cross-linking and curing.
[0089] Figure 1 The results of the anti-protein adsorption performance of the polymer materials of Examples 1 to 6 in the form of coatings are shown, from which it can be seen that the polymer material of Example 1 has the best anti-protein adsorption performance.
[0090] Example 7
[0091] Preparation of PS / SCA-PEG-PS / SCA-105 (PSES105-Si) non-degradable antifouling materials and coatings
[0092] 1. The preparation process of the macromolecular initiator (Br-PEG-Br) is the same as that in Example 1.
[0093] 2. Synthesis of triblock polymers with silane coupling agents as crosslinking sites:
[0094] The reaction needs to be carried out under anhydrous and oxygen-free conditions. The 100mL reaction tube is connected to a double-row tube, and the bottle is baked with a hot spray gun under vacuum conditions to remove water. After three gas exchanges, argon protection is maintained. The mass proportion of the polyethylene glycol block in PSES105-Si is 20%. According to calculations, 33mg of catalyst CuBr, 300mg of Br-PEG-Br, 0.86mL of styrene monomer (St.), and 130μL of TMSPMA monomer are added to the reaction tube in sequence. After one freeze-thaw, 98mg of ligand Bpy is added, and three freeze-thaw cycles are continued to fully deoxygenate. The reaction system is then placed in a 100°C oil bath for continuous reaction for about 6 hours, the reaction is terminated and post-processed to obtain a triblock polymer (PSES105-Si) with a number average molecular weight of about 5000.
[0095] 3. Preparation of biological antifouling coating and bulk materials:
[0096] Take the substrate to be modified (silicon wafer, glass sheet, etc.) and perform plasma cleaning; dissolve the polymer PSES105-Si in ethyl acetate (EA) to prepare a polymer solution concentration of 10 mg / mL, and use spin coating technology to obtain a uniform coating with nanometer thickness on the substrate, and then place it in a hot oven at 50°C for 1 hour for cross-linking and curing.
[0097] For the preparation of anti-fouling bulk materials, the casting method is taken as an example: take a mold of appropriate size (such as a tetrafluoroethylene mold, etc.), dissolve the polymer PSES105-Si in THF, prepare a 400 mg / mL polymer concentrated solution, take an appropriate amount of polymer solution to fill the mold, evaporate the solvent under natural conditions, and then place it in a hot oven at 50°C for 1 hour for cross-linking and curing.
[0098] Example 8
[0099] Preparation of PS / SCA-PEG-PS / SCA-110 (PSES110-Si) non-degradable antifouling materials and coatings
[0100] 1. The preparation process of the macromolecular initiator (Br-PEG-Br) is the same as that in Example 1.
[0101] 2. Synthesis of triblock polymers with silane coupling agents as crosslinking sites:
[0102] The reaction needs to be carried out under anhydrous and oxygen-free conditions. The 100mL reaction tube is connected to a double-row tube, and the bottle is baked with a hot spray gun under vacuum conditions to remove water. After three gas exchanges, argon protection is maintained. The mass proportion of the polyethylene glycol block in PSES110-Si is 10%. According to calculations, 70mg of catalyst CuBr, 631mg of Br-PEG-Br, 4.1mL of styrene monomer (St.), and 625μL of TMSPMA monomer are added to the reaction tube in sequence. After one freeze-thaw, 210mg of ligand Bpy is added, and three freeze-thaw cycles are continued to fully deoxygenate. The reaction system is then placed in a 100°C oil bath for continuous reaction for about 6 hours, the reaction is terminated and post-processed to obtain a triblock polymer (PSES110-Si) with a number average molecular weight of about 10,000.
[0103] 3. Preparation of biological antifouling coating and bulk materials:
[0104] Take the substrate to be modified (silicon wafer, glass wafer, etc.) and perform plasma cleaning; dissolve the polymer PSES110-Si in ethyl acetate (EA) to prepare a polymer solution concentration of 10 mg / mL, and use spin coating technology to obtain a uniform coating with nanometer thickness on the substrate, and then place it in a hot oven at 50°C for 1 hour for cross-linking and curing.
[0105] For the preparation of anti-fouling bulk materials, the casting method is taken as an example: take a mold of appropriate size (such as a tetrafluoroethylene mold, etc.), dissolve the polymer PSES110-Si in THF, prepare a 400 mg / mL polymer concentrated solution, take an appropriate amount of polymer solution to fill the mold, evaporate the solvent under natural conditions, and then place it in a hot oven at 50°C for 1 hour for cross-linking and curing.
[0106] Example 9
[0107] Preparation of PMMA / SCA-PEG-PMMA / SCA-105 (PMEM105-Si) non-degradable antifouling materials and coatings
[0108] 1. The preparation process of the macromolecular initiator (Br-PEG-Br) is the same as that in Example 1.
[0109] 2. Synthesis of triblock polymers with silane coupling agents as crosslinking sites:
[0110] The reaction needs to be carried out under anhydrous and oxygen-free conditions. The 100mL reaction tube is connected to a double-row tube, and the bottle is baked with a hot spray gun under vacuum conditions to remove water. After three gas exchanges, argon protection is maintained. The mass proportion of the polyethylene glycol block in PMEM105-Si is 20%. According to calculations, 66mg of the catalyst CuBr, 600mg of Br-PEG-Br, 2.17mL of methyl methacrylate monomer (MMA), and 345μL of ultra-dry 1,4-dioxane solution of TMSPMA monomer are added to the reaction tube in sequence. After one freeze-thaw, 200mg of the ligand Bpy is added, and three freeze-thaw cycles are continued to fully remove oxygen. The reaction system is then placed in a 100℃ oil bath for continuous reaction for about 6h, the reaction is terminated and post-processed to obtain a triblock polymer (PMEM105-Si) with a number average molecular weight of about 5000.
[0111] 3. Preparation of biological antifouling coating and bulk materials:
[0112] Take the substrate to be modified (silicon wafer, glass sheet, etc.) and perform plasma cleaning; dissolve the polymer PMEM105-Si in THF to prepare a polymer solution concentration of 10 mg / mL, and use spin coating technology to obtain a uniform coating with nanometer thickness on the substrate, and then place it in a hot oven at 50°C for 1 hour for cross-linking and curing.
[0113] For the preparation of anti-fouling bulk materials, the casting method is taken as an example: take a mold of appropriate size (such as a tetrafluoroethylene mold, etc.), dissolve the polymer PMEM105-Si in THF, prepare a 400 mg / mL polymer concentrated solution, take an appropriate amount of polymer solution to fill the mold, evaporate the solvent under natural conditions, and then place it in a hot oven at 50°C for 1 hour for cross-linking and curing.
[0114] Example 10
[0115] Preparation of PMMA / SCA-PEG-PMMA / SCA-110 (PMEM110-Si) non-degradable antifouling materials and coatings
[0116] 1. The preparation process of the macromolecular initiator (Br-PEG-Br) is the same as that in Example 1.
[0117] 2. Synthesis of triblock polymers with silane coupling agents as crosslinking sites:
[0118] The reaction needs to be carried out under anhydrous and oxygen-free conditions. The 100mL reaction tube is connected to a double-row tube, and the bottle is baked with a hot spray gun under vacuum conditions to remove water. After three gas exchanges, argon protection is maintained. The mass proportion of the polyethylene glycol block in PMEM110-Si is 10%. According to calculations, 25 mg of the catalyst CuBr, 200 mg of Br-PEG-Br, 1.65 mL of methyl methacrylate monomer (MMA), and 256 μL of TMSPMA monomer in ultra-dry 1,4-dioxane solution are added to the reaction tube in sequence. After one freeze-thaw, 70 mg of the ligand Bpy is added, and three freeze-thaw cycles are continued to fully remove oxygen. The reaction system is then placed in a 100°C oil bath for continuous reaction for about 6 hours, the reaction is terminated and post-processed, and a triblock polymer (PMEM110-Si) with a number average molecular weight of about 10,000 can be obtained.
[0119] 3. Preparation of biological antifouling coating and bulk materials:
[0120] Take the substrate to be modified (silicon wafer, glass wafer, etc.) and perform plasma cleaning; dissolve the polymer PMEM110-Si in THF to prepare a polymer solution concentration of 10 mg / mL, and use spin coating technology to obtain a uniform coating with nanometer thickness on the substrate, and then place it in a hot oven at 50°C for 1 hour for cross-linking and curing.
[0121] For the preparation of anti-fouling bulk materials, the casting method is taken as an example: take a mold of appropriate size (such as a tetrafluoroethylene mold, etc.), dissolve the polymer PMEM110-Si in THF, prepare a 400 mg / mL polymer concentrated solution, take an appropriate amount of polymer solution to fill the mold, evaporate the solvent under natural conditions, and then place it in a hot oven at 50°C for 1 hour for cross-linking and curing.
[0122] Comparative Example 1
[0123] Preparation of PEG-PBMA / SCA-110 (PEB110-Si) non-degradable antifouling materials and coatings
[0124] 1. Preparation of macromolecular initiator (single-end brominated PEG, PEG-Br):
[0125] Take 2.5g of polyethylene glycol monomethyl ether with a number average molecular weight of 1000 and dissolve it in dichloromethane in a 100mL round-bottom flask, and add a certain amount of anhydrous sodium sulfate to bind the water in the system. Add 2.1mL of triethylamine TEA, an acid binding agent, to the flask, add 0.95mL of bromoisobutyryl bromide dropwise to the flask under stirring in an ice-water bath, and then react at room temperature for 12h. After terminating the reaction, use extraction to remove impurities, and precipitate with ice ether to obtain the product PEG-Br.
[0126] 2. Synthesis of diblock polymers with silane coupling agents as crosslinking sites:
[0127] The reaction needs to be carried out under anhydrous and oxygen-free conditions. The 100mL reaction tube is connected to a double-row tube, and the bottle is baked with a hot spray gun to remove water under vacuum conditions. After three gas exchanges, argon protection is maintained. The mass proportion of the polyethylene glycol block in PEB110-Si is 10%. According to calculations, 167mg of the catalyst CuBr, 0.78g of PEG-Br, 6.7mL of BMA monomer, and 1mL of TMSPMA monomer in anhydrous ethanol solution are added to the reaction tube in sequence. After a freeze-thaw operation, 487mg of the ligand Bpy is added, and three freeze-thaw operations are continued to fully deoxygenate. The reaction system is then placed in a 70°C oil bath for continuous reaction for about 12 hours, the reaction is terminated and post-processed to obtain a diblock polymer (PEB110-Si) with a number average molecular weight of about 10,000.
[0128] 3. Preparation of biological antifouling coating:
[0129] Take the substrate to be modified (silicon wafer, glass wafer, etc.) and perform plasma cleaning; dissolve the polymer PEB110-Si in THF to prepare a polymer solution concentration of 10 mg / mL, and use spin coating technology to obtain a uniform coating with nanometer thickness on the substrate, and then place it in a hot oven at 50°C for 1 hour for cross-linking and curing.
[0130] For the preparation of anti-fouling bulk materials, the casting method is taken as an example: take a mold of appropriate size (such as a tetrafluoroethylene mold, etc.), dissolve the polymer PEB110-Si in THF, prepare a 400 mg / mL polymer concentrated solution, take an appropriate amount of polymer solution to fill the mold, evaporate the solvent under natural conditions, and then place it in a hot oven at 50°C for 1 hour for cross-linking and curing.
[0131] Figure 2 The anti-protein adsorption performance of the diblock polymer material of Comparative Example 1 and the triblock polymer material of Example 2 in the form of coating is demonstrated, and it can be seen that the polymer material of Example 2 has more excellent anti-protein adsorption performance.
[0132] Take the TPU substrate to be modified and perform plasma cleaning; dissolve the polymer of comparative example 1 or the polymer of example 2 in THF to prepare a polymer solution concentration of 10 mg / mL, and use spin coating technology to obtain a uniform coating of nanometer thickness on the substrate, and then place it in a hot oven at 50°C for 1 hour for cross-linking and curing to obtain the coating of comparative example 1 and the coating of example 2, respectively, and then use the substrate material TPU as a control to perform anti-platelet adhesion performance test, the results are shown in Figure 3 It can be seen that the polymer material of Example 2 has more excellent anti-platelet adhesion performance.
[0133] Poly(ethylene glycol) diacrylate with a number average molecular weight of 10,000 and photoinitiator I2959 were dissolved in deionized water to prepare a polymer solution with a concentration of 400 mg / mL, which was poured into a mold and polymerized under ultraviolet light to form a PEGDA gel material. Figure 4 The tensile strength of the PEGDA gel material and the triblock polymer material of Example 2 is demonstrated, and it can be seen that the polymer material of Example 2 has better tensile properties.
[0134] In addition, it should be understood that after reading the above description of the present invention, those skilled in the art may make various changes or modifications to the present invention, and these equivalent forms also fall within the scope defined by the claims attached to this application.
Claims
1. A non-degradable protein-resistant material, characterized in that: The non-degradable anti-protein adsorption material is a block polymer with a silane coupling agent as a cross-linking site or a material formed by cross-linking materials including the block polymer; The block polymer is non-degradable, and the molecular chain composition includes a polyethylene glycol hydrophilic segment, a hydrophobic segment introduced by a hydrophobic monomer, and a cross-linked segment introduced by a cross-linked monomer, wherein the polyethylene glycol hydrophilic segment is located between the hydrophobic segments, the hydrophobic segment includes a methacrylate segment, an aromatic substituted polyolefin segment or a combination thereof, and the cross-linked monomer is a silane coupling agent with a carbon-carbon double bond; The number average molecular weight of the polyethylene glycol hydrophilic segment is 100 to 10000 g / mol, preferably 800 to 4000 g / mol; The mass proportion of the polyethylene glycol hydrophilic segment in the block polymer is 5% to 50%, preferably 10% to 40%.
2. The non-degradable protein-resistant material according to claim 1, characterized in that: The hydrophobic monomer includes an olefinic monomer, and the olefinic monomer includes at least one of methyl methacrylate, ethyl methacrylate, propyl methacrylate, butyl methacrylate, hexyl methacrylate, octyl methacrylate, lauryl methacrylate, styrene, and phenylbutene; The crosslinking monomer includes at least one of 3-(isomethacryloyloxy)propyltrimethoxysilane, methacryloxypropyltriethoxysilane, 3-trimethoxysilane propyl acrylate, allyltrimethylsilane, vinyltri(β-methoxyethoxy)silane, vinyltrimethoxysilane, and A-151 silane coupling agent.
3. The non-degradable protein-resistant material according to claim 1, characterized in that: The sum of the mass proportions of the hydrophobic segments and the cross-linked segments in the block polymer is 50% to 95%, preferably 60% to 90%; In the block polymer, the sum of the mass proportions of the polyethylene glycol hydrophilic segment, the hydrophobic segment and the cross-linked segment is 100%; The molar ratio of the hydrophobic monomer to the cross-linking monomer is 100:(5-20).
4. The non-degradable protein-resistant material according to claim 1, characterized in that: The block polymer is obtained by a controlled / living free radical polymerization reaction, and the controlled / living free radical polymerization reaction is an atom transfer radical polymerization reaction; The raw materials of the controlled / active free radical polymerization reaction include olefin monomers, crosslinking monomers and terminal functionalized polyethylene glycol, wherein the olefin monomers are used for polymerization to form hydrophobic segments, and the terminal functionalized polyethylene glycol is used for reaction to form polyethylene glycol hydrophilic segments; The raw materials also include a catalyst and a ligand; The catalyst includes cuprous halide; The dosage of the catalyst is 1.1 to 3 times the molar amount of the functionalized end groups in the terminal functionalized polyethylene glycol; The ligand includes at least one of 2,2'-bipyridine and pentamethyldiethylenetriamine; The dosage of the ligand is 2.5 to 7.5 times the molar amount of the functionalized terminal groups in the terminal functionalized polyethylene glycol.
5. The non-degradable protein-resistant material according to claim 4, characterized in that: When the block polymer is prepared by controlled / living free radical polymerization, the amount of the crosslinking monomer added in one step is 5% to 20% of the molar amount of the olefin monomer in the same batch.
6. The non-degradable anti-protein adsorption material according to claim 4, characterized in that: The temperature of the controlled / living free radical polymerization reaction is 50 to 75° C., and the time is 5 to 20 hours.
7. The non-degradable protein-resistant material according to claim 1, characterized in that: The cross-linking temperature of the material is 45-55°C.
8. The method for preparing the non-degradable protein-resistant adsorption material according to any one of claims 1 to 7, characterized in that: include: preparing olefin monomers, cross-linking monomers and terminal functionalized polyethylene glycol, wherein the olefin monomers are used for polymerization to form hydrophobic segments, and the terminal functionalized polyethylene glycol is used for reaction to form polyethylene glycol hydrophilic segments; The block polymer is obtained by subjecting raw materials including olefin monomers, crosslinking monomers and terminal functionalized polyethylene glycol to controlled / living free radical polymerization; or, After the block polymer is obtained according to the above process, the non-degradable protein-resistant adsorption material is further obtained by thermal cross-linking.
9. Use of the non-degradable anti-protein adsorption material according to any one of claims 1 to 7 in the field of anti-protein adsorption.
10. The use according to claim 9, characterized in that: The non-degradable anti-protein adsorption material is used as a bulk material and / or a coating material for anti-protein adsorption.
Citation Information
Patent Citations
PtBA-b-PEG-b-PtBA block copolymer, and preparation method and application thereof
CN102731736A
Protein-adsorption-resistant self-cleaning block copolymer as well as preparation method and application thereof
CN111533865A
Method for preparing an amphiphilic diblock and triblock copolymer having a hydrophilic block and one or two hydrophobic blocks, method for preparing an organic mesoporous material using this copolymer, and material this prepared
WO2008129213A1
Cited By
Functional polymer for reducing biological pollution on surface of material, preparation method of functional polymer and preparation method of functional polymer coating
CN122563025A